The lexical profile of forestry academic texts: What does it take to understand a specialized discipline? - Guihua Luo; Jiamiao Song; Jingjing Wu (PLoS ONE)
Vocabulary is essential for comprehension, especially in specialized disciplines. However, the research on the lexical features of forestry remains underexplored. This study focuses on the vocabulary frequency profile of forestry academic texts, and compares forestry vocabulary with general vocabulary and general academic vocabulary. Using Range software and the BNC/COCA word lists, this research analyzed a corpus of 331 research articles and 14 textbooks across eight forestry sub-disciplines. Results demonstrate a rich and diverse vocabulary in this discipline. Two forestry-specific word lists, the forestry Latin loan word list and the forestry English word list, were developed from words not included in the BNC/COCA word lists. The analysis indicates that mastering the top 5,000 word families and four supplementary word lists from the expanded BNC/COCA word lists provides 95% lexical coverage of the forestry academic corpus. For 98% coverage, prioritizing the two forestry-specific word lists reduces the required word families from 11,000 to 8,000. While both forestry research articles and textbooks need 5,000 word families for 95% coverage, research articles require an additional 2,000 for 98% coverage. Lexical demands across sub-disciplines range from 4,000 to 6,000 word families for 95% coverage, and from 8,000 to 11,000 for 98% when including the forestry-specific word lists. Furthermore, findings also indicate that the forestry vocabulary contains a higher proportion of mid- and low-frequency words than general vocabulary and general academic vocabulary. These findings provide important guidance for setting vocabulary learning goals and sequences for learners in the forestry discipline, thereby contributing to improved comprehension of forestry academic texts and enhancing the effectiveness of English for Specific Purposes instruction.